An Integrated Analysis of mRNA and lncRNA Expression Profiles Indicates Their Potential Contribution to Brown Fat Dysfunction With Aging - Feng, Jie; Xu, Haoqin; Pan, Fenghui; Hu, Jiaojiao; Wu, Yulin; Lin, Ning; Zhang, Xiaoxiao; Ji, Chenbo; Hu, Yun; Zhong, Hong; Yan, Linping; Zhong, Tianying; et al. (Frontiers in Endocrinology, 2020)
Brown adipose tissue (BAT) can convert fatty acids and glucose into heat, exhibiting the potential to combat obesity and diabetes. The mass and activity of BAT gradually diminishes with aging. As a newly found regulator of gene expression, long non-coding RNAs (lncRNAs) exhibit a wide range of functions in life processes. However, whether long non-coding RNA (lncRNA) involves in BAT dysfunction with aging is still unclear. Here, using RNA-sequencing technology, we identified 3237 messenger RNAs (mRNAs) and 1312 lncRNAs as differentially expressed in BAT of 10-month-old mice compared with 6- to 8-week-old. The protein-protein interaction network and k-score analysis revealed that the core mRNAs were associated with two important aging-related pathways, including cell cycle and p53 signalling pathway. Gene set enrichment analysis indicated that these mRNAs might participate in lipid metabolism and brown fat dysfunction. Functional enrichment analyses demonstrated that dysregulated lncRNAs were associated with mitochondria, regulation of cellular senescence, cell cycle, metabolic and p53 signalling pathways. Moreover, we revealed that two lncRNAs (NONMMUT024512 and n281160) may involve in the regulation of their adjacent gene peroxisome proliferator-activated receptor alpha (Pparα), a thermogenesis regulator. Collectively, these results lay a foundation for extensive studies on the role of lncRNAs in age-related thermogenic degradation.